DIGITAL CULTURE, TEACHING WORK IMAGINARY AND TEACHING PROFESSIONALIZATION: THE RITA SERIES - Penteado, Regina Zanella [UNESP]; Budin, Clayton José; Costa, Belarmino Cesar Guimarães da (FapUNIFESP (SciELO), 2022)
This documentary research aims to identify imagery in teaching expressed / disseminated in the Rita series (Netflix, by streaming), whose main character is a teacher. From the analysis, the imagery in teaching emerged: solitary and individualized; temporized, regulated and routinized; conflictive; technical; apart from social debate and with traditional pedagogical practices; subjected to authoritarian, competitive, threatening, disciplinary and punitive relationships. Such imagery correspond to old teaching concepts (such as vocation and craft) and to a teaching socialization marked by feminization - as opposed to contemporary forms of teaching and the idea of teaching as a profession. The approach considers the context of the digital culture that focuses on the forms of perception and representation of teaching in the public space of education, expressing/disseminating the imagery that clutter the social debate of teaching professionalization.
CULTURA DIGITAL, IMAGINARIOS DEL TRABAJO DOCENTE Y LA PROFESIONALIZACIÓN DE LA ENSEÑANZA: LA SERIE RITA
Cultura digital, imaginários de trabalho docente e a profissionalização do ensino: a série Rita
Keywords: Digital culture; Teacher education; Teaching professionalization; Teaching socialization; Teaching work